2022
DOI: 10.1212/nxi.0000000000001117
|View full text |Cite|
|
Sign up to set email alerts
|

Siponimod Inhibits the Formation of Meningeal Ectopic Lymphoid Tissue in Experimental Autoimmune Encephalomyelitis

Abstract: Background and ObjectivesTo investigate whether the formation or retention of meningeal ectopic lymphoid tissue (mELT) can be inhibited by the sphingosine 1-phosphate receptor 1,5 modulator siponimod (BAF312) in a murine model of multiple sclerosis (MS).MethodsA murine spontaneous chronic experimental autoimmune encephalomyelitis (EAE) model, featuring meningeal inflammatory infiltrates resembling those in MS, was used. To prevent or treat EAE, siponimod was administered daily starting either before EAE onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Numerous studies using anti-CD20 antibodies and other drugs [ 52 , 58 , 59 , 60 ] have shown that early treatment (before EAE onset or at the time point of EAE onset) typically prevents or significantly diminishes EAE development onset. This is not surprising because early interference with the immune response induced by immunization also affects the later development of CNS pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using anti-CD20 antibodies and other drugs [ 52 , 58 , 59 , 60 ] have shown that early treatment (before EAE onset or at the time point of EAE onset) typically prevents or significantly diminishes EAE development onset. This is not surprising because early interference with the immune response induced by immunization also affects the later development of CNS pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This small molecule can also cross the BBB and reach the CNS parenchyma as well as the meninges, thereby it could block lymphocyte migration to the meningeal compartment. Siponimod reduced EAE severity and halted the formation of meningeal ectopic lymphoid follicles [ 146 ]. It is still under debate if the reduction of this meningeal compartmentalized inflammation is enough to reduce the clinical symptoms of progressive MS, or if in the case of siponimod, other secondary effects have roles.…”
Section: Effects Of Ms Therapies On B Cell Migrationmentioning
confidence: 99%
“…Interestingly the DMT siponimod, which is licenced for SPMS, was found to reduce the formation of meningeal lymphoid structures in a mouse model of EAE [ 138 ]. It was observed that when siponimod was administered prior to EAE onset, formation of TLS was reduced.…”
Section: Therapeutic Strategies Targeting Meningeal Inflammation and Tlsmentioning
confidence: 99%